Association of behaviour change techniques with effectiveness of dietary interventions among adults of retirement age: a systematic review and meta-analysis of randomised controlled trials - Lara, Jose (BioMed Central, 2014)
BACKGROUND: There is a need for development of more effective interventions to achieve healthy eating, enhance healthy ageing, and to reduce the risk of age-related diseases. The aim of this study was to identify the behaviour change techniques (BCTs) used in complex dietary behaviour change interventions and to explore the association between BCTs utilised and intervention effectiveness. METHODS: We undertook a secondary analysis of data from a previous systematic review with meta-analysis of the effectiveness of dietary interventions among people of retirement age. BCTs were identified using the reliable CALO-RE taxonomy in studies reporting fruit and vegetable (F and V) consumption as outcomes. The mean difference in F and V intake between active and control arms was compared between studies in which the BCTs were identified versus those not using the BCTs. Random-effects meta-regression models were used to assess the association of interventions BCTs with F and V intakes. RESULTS: Twenty-eight of the 40 BCTs listed in the CALO-RE taxonomy were identified in the 22 papers reviewed. Studies using the techniques ‘barrier identification/problem solving’ (93 g, 95% confidence interval (CI) 48 to 137 greater F and V intake), ‘plan social support/social change’ (78 g, 95%CI 24 to 132 greater F and V intake), ‘goal setting (outcome)’ (55 g 95%CI 7 to 103 greater F and V intake), ‘use of follow-up prompts’ (66 g, 95%CI 10 to 123 greater F and V intake) and ‘provide feedback on performance’ (39 g, 95%CI −2 to 81 greater F and V intake) were associated with greater effects of interventions on F and V consumption compared with studies not using these BCTs. The number of BCTs per study ranged from 2 to 16 (median = 6). Meta-regression showed that one additional BCT led to 8.3 g (95%CI 0.006 to 16.6 g) increase in F and V intake. CONCLUSIONS: Overall, this study has identified BCTs associated with effectiveness suggesting that these might be active ingredients of dietary interventions which will be effective in increasing F and V intake in older adults. For interventions targeting those in the peri-retirement age group, ‘barrier identification/problem solving’ and ‘plan for social support/social change’ may be particularly useful in increasing the effectiveness of dietary interventions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12916-014-0177-3) contains supplementary material, which is available to authorized users.